Impression, projection : une histoire médiatique entre cinéma et journalisme - Bégin, Richard; Carrier-Lafleur, Thomas, 1986-; Simard-Houde, Mélodie, 1986- (Quebec : Les Presses de l'Université Laval, 2019)
[Machine translated] The cinema and the press have always had a large number of elective affinities, just as they have always been in competition. Their broadcast channels and platforms are constantly intersecting, from the news filmed from the early 20th century to the participatory journalism of Web 2.0. Their materials and language are also full of hybridities and exchanges, whether journalism invests small and large screens or that the cinema absorbs the journalistic matter. New cinematographic genres - such as cinematic and film-inquiry - and journalistic genres - such as film criticism - have emerged. To these remedies are added reciprocal representations, the cinema having continually put journalism to the test, journalism having participated in the advent as well as the institutionalization of the cinema. Through alliances and rivalries, correspondences and contradictions, simultaneities and reversals, this volume proposes to explore the continual redefinition of our media and their identities. The cinema and the press have always had a large number of elective affinities, just as they have always been in competition. Their broadcast channels and platforms are constantly intersecting, from the news filmed from the early 20th century to the participatory journalism of Web 2.0. Their materials and language are also full of hybridities and exchanges, whether journalism invests small and large screens or that the cinema absorbs the journalistic matter. New cinematographic genres - such as cinematic and film-inquiry - and journalistic genres - such as film criticism - have emerged. To these remedies are added reciprocal representations, the cinema having continually put journalism to the test, journalism having participated in the advent as well as the institutionalization of the cinema. Through alliances and rivalries, correspondences and contradictions, simultaneities and reversals, this volume proposes to explore the continual redefinition of our media and their identities.
Online resource; title from digital title page (viewed on December 13, 2019).
eBooks on EBSCOhost
Keywords: Mass media; World Wide Web; Journalism; Motion pictures; Identity (Philosophical concept); Digital media; Internet; Journalism; Motion Pictures; Médias.; Web; Journalisme; Identité.; Médias numériques.; Cinéma.; mass media; World Wide Web; journalism; identity; LANGUAGE ARTS & DISCIPLINES -- Journalism; Digital media; Identity (Philosophical concept); Journalism; Mass media; Motion pictures; World Wide Web